The implementation of lean practices in Malaysian food manufacturers - Repin, Muhamad Fadzil; Sharifuddin, Juwaidah; Shamsudin, Mad Nasir; Ali, Fazlin (Pergamon Press, 2022)
Lean practices was introduced to the manufacturing industry to improved manufacturing performance. The new business model in food manufacturing performance focuses on elimination of waste, high quality packaging and branding system, efficient logistics and procurement, high value-added products, and lower operating costs. Research on lean practices has received much attention with contradictory findings. However, research on measuring lean practices that affect manufacturing performance, especially in food manufacturing, has received little attention. Based on the literature reviewed, it was found that there are three important lean practices concept: the right product is at the right time and location Just-in-time (JIT), waste reduction (Elimination of Waste) and continuous improvement (Kaizen) can affect manufacturing performance. Products and services are always expected to be derived on time to ensure low-cost production and flexibility, by reducing non-value-adding operations or “waste” while fulfilling customers’ needs. The survey was conducted through face-to-face interview and e-mail correspondence. There were 282 companies involved as the respondents of the study. The Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were performed to test the construct validity or to “confirm” the construct and to test model fits. The findings validated the significant effects of manufacturing lean practices on manufacturing performances in Malaysia’s food manufacturing companies on all variables.